Perbedaan Dimensi Benda Uji Terhadap Kuat Tekan Beton - Erliana, Hilma; Yusra, Cut Liliiza; Dwinta, Ade; Hasdanita, Fitry (Akademi Komunitas Negeri Aceh Barat, 2024)
AbstractConcrete is one of the most widely used construction materials in various types of buildings and infrastructure. One of the critical factors in the quality of concrete is its compressive strength, which is measured through testing using cube- or cylinder-shaped specimens. Although testing standards have been established, the test results between these two specimen shapes often show significant differences. Therefore, this study aims to analyze the influence of specimen dimensions and shapes on the results of concrete compressive strength tests. The research was conducted at the Foundation Construction, Concrete, and Road Paving Laboratory at the Aceh Barat State Community Academy, using materials such as Andalas Portland cement, concrete sand, gravel, and water from the laboratory. The tests were performed according to SNI methods on cube and cylinder specimens at different concrete ages (7, 14, and 28 days). The results showed that the average compressive strength of both cylinder and cube samples increased with the age of the concrete. At 28 days, the average compressive strength of the cylinder was 17.243 MPa, while the cube reached 20.821 MPa. The ratio between the compressive strengths of the cylinder and the cube (f'c/f'ck) ranged from 0.825 to 0.837, indicating that the cylinder's compressive strength was about 83% of the cube's. The difference in compressive strength between the cylinder and cube specimens is influenced by stress distribution during testing, which is affected by the shape and dimensions of the specimens. Meanwhile, the compressive strength ratio between these two specimen shapes remained stable across different concrete ages, suggesting that the difference in specimen shape consistently affects the compressive strength test results.Keywords: Specimen dimensions, Compressive strength, Cube, Cylinder AbstrakBeton merupakan salah satu bahan konstruksi yang paling sering digunakan dalam berbagai jenis bangunan dan infrastruktur. Salah satu faktor penting dalam kualitas beton adalah kuat tekan, yang diukur melalui pengujian menggunakan benda uji berbentuk kubus atau silindris. Meskipun standar pengujian telah ditetapkan, hasil uji antara kedua bentuk benda uji ini sering menunjukkan perbedaan signifikan. Oleh karena itu, penelitian ini bertujuan untuk menganalisis pengaruh dimensi dan bentuk benda uji terhadap hasil pengujian kuat tekan beton. Penelitian ini dilakukan di Laboratorium Konstruksi Pondasi, Beton, dan Pengaspalan Jalan pada Akademi Komunitas Negeri Aceh Barat, menggunakan material seperti semen Portland Andalas, pasir beton, split, dan air dari laboratorium tersebut. Pengujian dilakukan dengan menggunakan metode SNI untuk benda uji kubus dan silinder pada berbagai usia beton (7, 14, dan 28 hari). Hasil menunjukkan bahwa kuat tekan rata-rata sampel berbentuk silinder dan kubus meningkat seiring dengan bertambahnya umur beton. Pada umur 28 hari, kuat tekan rata-rata silinder adalah 17,243 MPa, sementara kubus mencapai 20,821 Mpa. Rasio antara kuat tekan silinder dan kubus (f'c/f'ck) berada pada kisaran 0,825 hingga 0,837, menunjukkan bahwa kuat tekan silinder sekitar 83% dari kuat tekan kubus. Perbedaan kuat tekan menunjukkan bahwa antara benda uji silinder dan kubus dipengaruhi oleh distribusi tegangan selama pengujian, yang disebabkan oleh perbedaan bentuk dan dimensi sedangkan Rasio kuat tekan antara kedua bentuk benda uji ini tetap stabil pada berbagai usia beton, menunjukkan bahwa perbedaan bentuk benda uji memberikan pengaruh yang konsisten terhadap hasil uji kuat tekan.Kata Kunci:Dimensi benda uji, Kuat tekan, kubus, silinder